The Effect of Message Source Credibility and Discount Framing on Purchase Intention of Emina Products with Brand Image as Mediation - Tazkiya Salsabillah; Savitri Ariani; Aang Curatman; Farah Noor Ayuningtyas (International Journal of Business, Economics, and Social Development, 2025)
The development of the beauty industry in Indonesia is driven by the increasing use of social media and e-commerce. Emina is one of the local brands that attracts attention, especially for teenagers in considering purchasing beauty products. This study aims to analyze the effect of message source credibility and discount framing on purchase intention of Emina products, with brand image as a mediating variable. A quantitative approach was used through an online survey with a total sample of 217 respondents and data analysis was carried out using the Partial Least Square Structural Equation Modeling (PLS-SEM) technique. The results show that message source credibiliy and discount framing have a positive and significant effect on purchase intention, both directly and indirectly through brand image as mediation.